Analisis Kelayakan Usaha Cairan Sabun Cuci Piring Studi Kasus PT Nirmala Resik Indonesia - Azzam Bachtiar Ardiyansyah; Fajar Alif Prakoso (RESWARA: Jurnal Riset Ilmu Teknik, 2023)
The household cleaning products industry, particularly liquid dishwashing soap, continues to experience steady growth driven by increasing domestic consumption and hygiene awareness. This study aims to analyze the business feasibility of liquid dishwashing soap production at PT Nirmala Resik Indonesia. The research employs a descriptive quantitative approach with a case study design. Data were collected through direct observation, interviews, and documentation of production and financial records. Business feasibility was evaluated using market, technical, and financial aspects, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Break Even Point (BEP) analyses. The results indicate that the liquid dishwashing soap business is feasible to operate and develop. Financial analysis shows a positive NPV, IRR exceeding the prevailing discount rate, and a relatively short payback period. From the technical aspect, production capacity, raw material availability, and technology utilization support business sustainability. Market analysis reveals stable demand and competitive pricing within the household cleaners sector. This study concludes that PT Nirmala Resik Indonesia’s liquid dishwashing soap business is economically viable and has strong growth potential. The findings provide practical implications for small and medium enterprises in evaluating similar household chemical product ventures.